DI-025 Dimethylfumarate for the treatment of multiple sclerosis: dosing regimen and safety data. (24th March 2015) - Rousseaux, D; Letreguilly, F; Bancourt, T; Lefebvre, A; Decourcelle, C; Floret, E
Abstract : Background: Dimethylfumarate is an oral treatment recently approved in France for the treatment of relapsing forms of multiple sclerosis at the recommended dose of 120 mg twice daily for 1 week then 240 mg twice daily. Purpose: To compare the prescribed starting dose of dimethylfumarate to the recommended one and to evaluate tolerability. Material and methods: For 3 months (May to July 2014), each new patient with a prescription for dimethylfumarate was included in the study. For these patients, we collected data about the disease (with medical software); the starting dose and questioned them about possible adverse event. Results: 30 patients were included (6 men and 24 women) with mean age of 46. Dimethylfumarate is prescribed as a second-line (17/30) or a third-line (13/30) treatment. The main reasons for prescribers to choose this treatment were: ineffective or contraindicated injectable drugs (37%), poor tolerability (23%) and fear of injections (20%). For 16 patients, the recommended starting dose was followed; the other 14 patients received a more gradual dosing regimen than that recommended. Regarding tolerability, adverse events reported more frequently by patients were flushing (50%), diarrhoea (20%) and abdominal pain (17%). 73% of patients had side effects whatever the starting dose (63% of those receiving the recommended dose and 85% of the others) but after one month, adverse events had stopped in 95% of these patients. During that study, 4 patients discontinued the treatment due to relapse of multiple sclerosis. Conclusion: This study shows that prescribers followed the recommended starting dose for only 53% of patients. A more gradual dosing regimen for the starting dose didn't seem to reduce the occurrence of side effects. It will be interesting to confirm this result by studying the frequency of occurrence of adverse events and using scales to assess quality of life compared to injectable treatments. References and/or acknowledgements: No conflict of interest.